Controle de qualidade da raiz de Operculina macrocarpa (Linn) Urb., Convolvulaceae - Michelin, Daniele Carvalho [UNESP]; Finati, Suellen Cristiane Gandolfo [UNESP]; Sacramento, Luis Vitor Silva [UNESP]; Vilegas, Wagner [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Springer Nature, 2010)
Considering the quality of the phytotherapic agents, it is important to point out that it includes rigorous attendance of the different steps of the development and production of these products, from the collection of the vegetable to the availability of the final product. In this work the quality control of the Operculina macrocarpa (Linn) Urb. roots, popularly known as 'batata-de-purga', was carried out. Pharmacopoeic and no pharmacopoeic methodologies were employed to physico-chemical and microbiological quality control. The obtained results showed that the roots presents a content of resin of 9,85%, The microbiological analysis did not present pathogenic growth among the other accomplished tests. The work stands out the importance of the establishment of norms for the quality control for the plants, so that they are found able to be used for phytotherapic reasons.
The quality control of Operculina macrocarpa (Linn) Urb. roots (Convolvulaceae)
Keywords: Convolvulaceae; Operculina macrocarpa; Quality control; resin; Escherichia coli; herbal medicine; medical literature; medicinal plant; methodology; microbial growth; pH; physical chemistry; phytotherapy; plant root; Pseudomonas aeruginosa; quality control; Salmonella; Staphylococcus aureus